محكم الهواري - نويهض, عادل (معجم أعلام الجزائر من صدر الإسلام حتى العصر الحاضر, 1980)
Keywords: Biographies; Hawwārī; Hūd b. Muḥkim al-

Le commentaire coranique de Hūd b. Muḥakkam/Muḥkim - Gilliot, Claude (Arabica, 1997)
Pp. 181-182: Hūd’s Tafsīr seems to be a kind of abstract of the Tafsīr of Yaḥyà b. Sallām al-Baṣrī (d. 200/815 in Egypt), who was born in 124/742 in Baṣra and who lived for a period of time in Kairouan. He was accused of being a Murji’ite.
Keywords: Coran – Commentaires – 9e siècle; Hawwārī; Hūd b. Muḥkim al-